Hubungan Persentase Serangan dengan Estimasi Kehilangan Hasil Akibat Serangan Hama Penggerek Buah Kopi Hypothenemus Hampei Ferr.(Coleoptera: Scolytidae) di Kabupaten Simalungun - Rahutdin P Purba; Darma Bakti; Suzanna F Sitepu (Jurnal Agroekoteknologi, 2015)
The objectives of the research was todetermine the relationship ofthe percentage of attackandestimateyield losses due toattack by coffee berryborer, HypothenemushampeiFerr. (Coleoptera: Scolytidae) inSimalungun district.This research used asurvey methodwith linear regression analysis between percentage of attack withpercentageloss of yield, regressionbetween the percentage of attack withpopulation densityand regressionbetweenpopulationdensity with percentageyield loss.The results showedthat thepopulationdensity ofpests onred fruithad asignificant relationship to thepercentageof yield lossin the red fruit,butthe percentage of attacksdid not havea significant relationship topopulation densityandthe percentage ofyield loss. The highestattack intensity(46.78%) wasin the DolokHuluanand the lowest(5.42%) wasin Bangun Saribu. The highest percentage of yield loss(17.25%) wasin SimpangHinalangand the lowest(8.45%) wasin BosiSinombah. The highestpopulationdensity(17.80) found inredfruitsand the lowest(6.32) was alsofound inred fruits.Keywords : coffee, percentage ofattack, Hypothenemus hampei Ferr.